Comprehensive health literacy in general populations – An international comparison. (30th September 2020) - Pelikan, J; Link, T; Berens, E; Pettersen, K; Le, C; Sørensen, K; Vogt, D; Gibney, S; Aringazina, A; Vrbovsek, S
Abstract: Background: The HLS-EU study in 2011 demonstrated for 8 EU Member States that there exists limited comprehensive health literacy for considerable proportions of the general population, that there is a social gradient for health literacy and that limited health literacy has problematic consequences for healthy lifestyles, self-reported health and utilization of professional health services. It was also shown that distributions and associations of health literacy differ considerable between countries. WHO-Europe started the Acton Network on Measuring Population and Organizational Health Literacy (M-POHL) to measure health literacy regularly with the Health Literacy Survey 2019 (HLS19). Methods: Based on the design and instrument of the HLS-EU study (to allow comparisons for countries participating in both surveys) a core questionnaire was developed for measuring comprehensive health literacy and its relevant correlates. Optional packages were created to measure, among others, digital health literacy and its most relevant correlates. Data were collected from probability samples of at least 1.000 respondents per country for the general population 18+ by personal interviews, telephone interviews or internet surveys in at least 15 member states of the WHO-Europe region. Results: Distributions for indices, scales and levels of comprehensive health literacy will be presented as well as correlations and regressions for associations of health literacy with social determinants and with consequences for selected life style indicators, indicators for self-reported health and use of professional health care services. Conclusions: Preliminary results show that the general trends of the HLS-EU study concerning health literacy hold true for HLS19 and that there are considerable differences between participating countries. Health literacy is relevant for health policy in all countries, but to understand the differences between countries a more detailed analysis is necessary.